(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Strut-free retaining wall systems offer important advantages for deep excavations, including improved construction efficiency, safety, and workspace availability. However, their application in excavations deeper than 20 m in soft clay remains limited. This study investigates the deformation behavior and optimal design parameters of a strut-free retaining wall system for a 30 m deep excavation in soft clay using three-dimensional finite element analysis. The retaining system consists of diaphragm walls, buttress walls, cross walls, and rib walls. A total of sixty-one numerical simulations were conducted to evaluate the influence of the number, thickness, and height of buttress and cross walls on wall deflection and ground settlement. The Hardening Soil model was adopted to represent the nonlinear behavior of soft clay, while structural components were modeled as elastic plate elements. The results indicate that increasing the number of buttress walls in the long excavation direction significantly reduces maximum wall deflection and surface settlement, whereas the effect in the short direction is relatively small. Among the investigated layouts, the configuration with two rib walls in the long direction and one in the short direction provided the most effective deformation control.